Adding Value to Livestock with Niche Meat Marketing Programs - Chad Carr; Larry Eubanks; Ryan Dijkhuis (EDIS, 2008)
AN197, a 6-page report by Chad Carr, Larry Eubanks, and Ryan Dijkhuis, discusses opportunities to add value to meat animals through existing specialty meat marketing programs and addresses potential challenges to developing a niche meat marketing program. Includes references. Published by the UF Department of Animal Sciences, April 2008.